Use of Zirconia Barrier in Guided Bone Regeneration: Clinical Case Report. - Erazo Vaca, Rafael Xavier; Núñez Huilcapi, Marjorie Selena; García Martínez, Emmy Nicole (Conexiones UG, 2025)
Following tooth loss, a considerable change [JC1.1]in the bone crest [JC2.1]occurs, known as [JC3.1]bone resorption. This is due to both changes in quantity and quality suffered by the affected area. Bone resorption is usually frequent and unavoidable, therefore resulting in dimensional changes in the alveolar ridge. Guided bone regeneration is based on the idea [JC4.1]of using a barrier to keep the blood clot stable and generate an area where bone tissue cells can develop without rapid interference from soft tissue cells. The use of zirconia barriers is a very viable alternative, since it is a biocompatible material that provides rigidity, durability, and clot stability. It can be considered a valid option in surgical bone regeneration procedures. It has been gaining significant clinical relevance due to its apparent superior advantages over different traditional materials used in membranes for the same purpose, such as titanium or polytetrafluoroethylene (PTFE) in terms of nonabsorbable membranes, although widely used worldwide by various clinicians. In addition [JC5.1]to its clinical indications, the advantage of being able to plan it digitally before clinical execution makes it one of the main reasons why it is considered ideal for regenerating bone [JC6.1]tissue in vertical and horizontal defects.